Purwarupa Ensiklopedi Upacara Adat Batak Toba - Tika, Maria; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2017)
The purpose of this paper is to describe the process of making the prototype of the encyclopaedia of traditional ceremonies of Batak Toba. The data collected using descriptive research methods with data gathering technique through interviews to customary leaders according to the focus of the problems studied. Based on the discussion, it can be concluded that the process of making the prototype of the encyclopedia of the ceremonies of Batak Toba as follows: (1) data gathering, that is technique to collect information about the ceremonies of Batak Toba, (2) design making in the form of chart in product to be made, and (3) the process of making the product in accordance with the work plan which contains the basic provisions of a topic that must be developed from the cover makingÂ  is the hard skin on the outside of the book containing the title of the book, and accompanied by several supporting images; the forewords contains the author acknowledgement, to those who have helped, the basis and purpose of making prototype of encyclopaedia, the hope, and the place, the month, and the year the book was made; the preliminary about the ceremonies in the Batak Tobaâ€™s ethnic; the main contents of the book contains articles on the ceremonies Batak Toba which includes the purpose, procession, place and time of the ceremonies, as well as data sources; an index is the list of words or terms in an alphabetical publication in the backyard; and informen biographies.Keywords: Batak Toba, prototype of encyclopedia, traditional ceremony.